Practice to deceive - Rule, Ann (New York Gallery Books, 2013)
"From the New York Times #1 bestselling author comes a riveting true-crime mystery set on a sleepy island in the Pacific Northwest: a man is murdered and the long list of suspects includes an aging beauty queen and her boyfriend. One wintery night on quiet Whidbey Island off the coast of Washington, Russ Douglas spent Christmas with his estranged wife, Brenna. She agreed to let him visit his children even though they were headed for divorce. He left Brenna Douglas's home in Langley on the morning of December 26, 2003 to run some errands. But hours passed and Russ didn't return home as he'd promised his children he would. Nor did he come back during the night. On the afternoon of December 27, a couple walking down a rural road noticed a vehicle in the driveway of a cabin. Since many of the places were vacant during the winter, neighbors kept an eye out for strangers. Curious, they walked up the cabin's driveway to check inside. They saw a man in the front seat, dead from a single gunshot wound to the head. They immediately put in a call to the Island County Sheriff's Office. The dead man was easily identified; it was Russell Douglas. But what came next in this homicide case surprised law enforcement and captured the attention of the entire town when the suspects included an aging beauty queen, her guitar-teacher lover, and Russell's widow, Brenna, owner of the local beauty salon. With her trademark aplomb, Ann Rule unravels the fascinating story of a murder, a small town, and a number of potential killers"--
"A man is murdered on a sleepy island, and three people are accused of murdering him: an aging beauty queen, her guitar-teacher lover, and the widow"--
The body in the woods -- Russ and Brenna -- The investigation -- Likely and unlikely suspects -- Mark Plumberg -- Peggy Sue Stackhouse -- The Stackhouse Family: 1963-2002 -- Arrest and punishment.
112854
Keywords: Murder -- Washington (State); Murder -- Investigation -- Washington (State); Trials (Murder) -- Washington (State); Murder -- Washington (State.); Murder -- Investigation -- Washington (State.); True Crime -- General; True Crime -- Murder -- General; Washington (State); True crime stories